Effects of ammonia stress in the Amazon river shrimp Macrobrachium amazonicum (Decapoda, Palaemonidae) - Pinto, Marcelo R.; Lucena, Malson N.; Faleiros, Rogerio Oliveira; Almeida, Eduardo Alves [UNESP]; McNamara, John C.; Leone, Francisco A. (Elsevier B.V., 2016)
We evaluate the effects of total ammonia nitrogen-N (TAN) exposure for 72 h on (Na+,K+)- and V(H+)-ATPase activities and on their subunit expressions in gills of the diadromous freshwater shrimp Macrobrachium amazonicum. Specific (Na+,K+)- and V(H+)-ATPase activities increased roughly 1.5- to 2 fold, respectively, after exposure to 2.0 mmol L-1 TAN. Quantitative RT-PCR analyses revealed a 2.5-fold increase in V(H+)-ATPase B subunit mRNA expression while (Na+,K+)-ATPase alpha-subunit expression was unchanged. Immunohistochemical analyses of the gill lamellae located the (Na+,K+)-ATPase throughout the intralamellar septal cells, independently of TAN concentration, while the V(H+)-ATPase was located in both the apical pillar cell flanges and pillar cell bodies. Systemic stress parameters like total hemocyte count decreased by 30% after exposure to 2.0 mmol L-1 TAN, accompanied by increased activities of the oxidative stress enzymes superoxide dismutase, glutathione reductase and glucose-6-phosphate dehydrogenase in the gills. The stress responses of M. amazonicum to elevated TAN include increases in gill (Na+,K+)- and V(H+)-ATPase activities that are accompanied by changes in oxidative stress enzyme activities, immune system effects and an increase in gill V(H+)-ATPase gene expression. These findings likely underpin physiological effects in a crustacean like M. amazonicum that exploits multiple ecosystems during its life cycle, as well as under culture conditions that may significantly impact shrimp production by the aquaculture industry. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Ammonia exposure; Gill microsome; (Na+, K+)-ATPase; V(H+)-ATPase; Gene expression; Oxidative enzymes; Macrobrachium amazonicum